A review of the pre-Pliocene penguins of New Zealand. Bulletin of the AMNH - Simpson, George Gaylord, 1902- (New York : [American Museum of Natural History], 1971)
p. 321-378 : ill., map 27 cm. Includes bibliographical references (p. 376-378). "The first fossil penguin to be made known, Palaeeudyptes antarcticus, was described from New Zealand by Thomas Henry Huxley in 1859. The many other pre-Pliocene penguins found in New Zealand after that date were monographed by Professor B.J. Marples in 1952. They are here systematically reviewed, with references to previous illustrations and substantive publications, and new data and illustrations are provided. Pre-Pliocene penguins have been found in New Zealand at ten localities or collecting areas. The generically unidentifiable specimen from Gore Bay, previously considered to be from the early Eocene and the oldest known penguin, is in fact Oligocene or early Miocene in age. The oldest known penguins are Pachydyptes ponderosus, Palaeeudyptes marplesi, and Palaeeudyptes sp. from the late Eocene. Other known New Zealand penguins range through the Oligocene and perhaps early Miocene. Within the range late Eocene-early Miocene many specimens are of undeterminable precise age. The reported great range, Kaiatan-Waitakian for the single species Palaeeudyptes antarcticus is not substantiated. The known pre-Pliocene New Zealand penguins are classified in six genera, Palaeeudyptes, Pachydyptes, Platydyptes, Archaeospheniscus, Duntroonornis, and Korora, with nine named species, of which ?Platydyptes marplesi is here new. Among fairly numerous specimens referred to Palaeeudyptes, only the two specific holotypes are considered definitely identifiable to species on the basis of present knowledge. It is unlikely that any of the known genera were ancestral to Recent penguins. Previous attempts at subfamily classification are unsatisfactory, and subfamilies are abandoned here. The New Zealand forms show some, but limited resemblances to the penguin faunas of each of the other three regions where fossils of this family have been found; southern Australia, Seymour Island, and Argentine Patagonia. The largest fossil penguin, Pachydyptes ...